Stripovska obravnava češkega narodnega preporoda - Niklesová, Eva (Slavistična revija, 2014)
The paper explores the comic book Šifra mistra Hanky (The Master Hanka Code), with special attention to the proportional representation of documentary component and fiction in its storyline. It is focused on the roles played by the two protagonists of the story, Václav Hanka and Josef Dobrovský. Furthermore, the paper examines educational utility of the text, as it blends factual and documentary information with mystification and fiction.
Keywords: "Kraljedvorski rokopis"; "Šifra mistra Hanky"; Czech literature; češka književnost; fiction; fikcija; Hanka, Václav, 1791-1861; Jerie, Karel; Matějíček, Tomáš Hibi, "Šifra mistra Hanky"; rokopisi; stripi; Zelenogorski rokopis